Emergency stations in the grand mosque of mecca as an application for wireless sensor networks - Latif A.I.; Othman M.; Ali N.B.; Al-Mayouf Y.R.B.; Mahdi O.A. (Asian Research Publishing Network, 2023)
During the annual Hajj pilgrimage, a large number of pilgrims suffer death as a result of misadventure and natural causes. Others, unfamiliar with the location, become lost in the crowds. As the demands of catering to the needs of ever-growing numbers of pilgrims visiting the Sacred Mosques increase, crowd control and communication between pilgrims and those responsible for the provision of services remains a significant issue for both the local authority and the pilgrims themselves. This paper reports how, in order to alleviate some of these problems, wireless sensor network stations should be established as emergency fixed stations. Such stations should be strategically situated throughout the holy mosque to assist rescue teams in locating and recovering lost pilgrims. Important factors in selecting the type of sensor are the power it consumes, its range and financial cost. The best combination of these factors can be found in the RF Engines sensor produced by Synapse. In modelling the network characteristics of this sensor in a variety of circumstances, the results demonstrate stability in sending and resaving packets with low rates of delay and dropped packet. In view of these results and due to the limited size of the network, high network performance can be anticipated. 2005 - 2016 JATIT & LLS. All rights reserved.